The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.19080/adoh.2018.07.555723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low- level laser therapy (LLLT) on Orthodontic Tooth Movement - Cellular Level

Abstract: Low level laser therapy's effect on main cellular components involved in orthodontic tooth movement: In the last few decades, researchers have attempted to determine the affect of LLLT on the biological pathways involved in orthodontic tooth movement. Some authors believe that LLLT induces osteoblasts proliferation (in vivo studies, [27][28] and in vitro studies [29][30][31][32][33][34][35][36][37][38]. Which is responsible for the accelerated tooth movement. However, according to other researchers, bone resor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Red-wavelength light has been widely accepted as a useful tool to stimulate tissue regeneration in light-based therapy. ,, ROS generation is one of the main molecular pathways involved in light-based therapy. , Although an adequate amount of ROS can induce ROS signaling to stimulate cellular changes, excessive ROS generation can damage cell function, resulting in apoptosis . As illustrated in Figure S2, 3D-cultured hMSCs (e.g., spheroids) have been discovered to show higher growth factor secretion and ROS tolerance than 2D-cultured hMSCs. ,, This means that spheroids in hMSCcx might be more suitable for secreting growth factors without excessive ROS generation when applying light-based therapy than hMSCcs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red-wavelength light has been widely accepted as a useful tool to stimulate tissue regeneration in light-based therapy. ,, ROS generation is one of the main molecular pathways involved in light-based therapy. , Although an adequate amount of ROS can induce ROS signaling to stimulate cellular changes, excessive ROS generation can damage cell function, resulting in apoptosis . As illustrated in Figure S2, 3D-cultured hMSCs (e.g., spheroids) have been discovered to show higher growth factor secretion and ROS tolerance than 2D-cultured hMSCs. ,, This means that spheroids in hMSCcx might be more suitable for secreting growth factors without excessive ROS generation when applying light-based therapy than hMSCcs.…”
Section: Resultsmentioning
confidence: 99%
“…Because light energy can be transferred to designated tissue or cells intact owing to its remote and penetrative properties, light has attracted significant attention as a strong tool for future biomedical technology. Light has also been adopted as a cell preconditioning tool because it induces the angiogenic secretive properties of cells by inducing ROS signaling. ,, ROS signaling in light therapy is achieved by ROS generation, following stimulation of cytochrome c oxidase in the mitochondria, which results in HIF-1α upregulation. , Because light can induce phototoxicity through excessive ROS generation, where ROS production exceeds elimination resulting in loss of ROS homeostasis, it is important to strike balance between ROS signaling and phototoxicity in light therapy. Therefore, excessive ROS generation normally induces apoptotic activity of the cells. , Therefore, the light dose must be adjusted so that the amount of ROS generated falls below the toxic range. …”
Section: Introductionmentioning
confidence: 99%
“…LLLT reduces gingival inflammation, and many studies indicate that LLLT has capacity to alter bone cellular behaviour [8,11]. Faster callus formation, revascularization, promotion of bone formation and denser trabecular networks have also been reported [12]. Liu et al investigated the healing of rat tibiae fractures irradiated with a lowlevel laser (830 nm, CW, 40 J/cm 2 once daily for five weeks) and suggested that LLLT causes an increase in callus volume [13].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of laser therapy on orthodontic treatment has been evaluated in several studies for better and faster tooth movement and for pain reduction during separator placement, archwire insertion, and canine retraction (4,31,32) .…”
Section: Discussionmentioning
confidence: 99%